Implementation And Analysis High Availability Network File System Based Server Cluster - Umam, Chaerul; Handoko, L. Budi; Rizqi, Ghulam Maulana (Jurnal Transformatika, 2018)
Server is a computer system that provides the kind of service in a computer network. One of the functions of the server is as data storage. Computers servers with high availability values are generally referred to as High Availability (HA) Server. HA enables a server can be operational in a sustainable manner for long periods of time. Now, HA has been combined with a cluster technique known as High Availability Clusters or failover cluster. In this research the author intends to apply, analyze, and implement a network file server that has a high availability of service. Researchers used a pacemaker as cluster resource management, Corosync as cluster messaging service and DRBD for the synchronization of data if a failover occurs and measured network performer cluster file system that does have a high availability service. The result is a network file system or the availability of the cluster has a value of 99.998% availability, which means it has a High Availability. The server network file system failover cluster meets the conditions, which, if the primary server (master) dies it will be replaced by a slave server.